Aktivitas Antimalaria Daun Erythrina variegata - Herlina, Tati; Supratman, Unang; Subarnas, Anas; Sutardjo, Supriyatna; Abdullah, Noor Rain (Jurnal Natur Indonesia, 2007)
The leaves of Erythrina variegata (Leguminosae) used tradisional plant of an antimalarial. In the course of our continuing search for novel an antimalarial compound from Erythrina plants, the methanol extract of the leaves ofE. variegata showed significant antimalarial activity in vitro toward Plasmodium falciparum in vitro using the lactate dehydrogenase (LDH) method. The methanol extract of the leaves of E. variegata showed against bothstrains of parasite with IC50of 6.8 ?g/ml against K1 and > 60 ?g/ml against 3D7, respectively. The methanol extract of the leaves of E. variegata was separated by using bioassay-guide fractionation. The n-buthanol fraction yieldedthe most activity, exhibiting equipotency against both strains of parasite with IC50of 5.1 ?g/ml against K1 and 13.5 ?g/ml against 3D7, respectively. Furthermore, by using the antimalarial activity to follow separation, the n-buthanol fraction was separated by combination of column chromatography to yield an active compound. The active compound showed antimalarial activity against both strains of parasite used with IC50 of 4.3 ?g/ml against K1 and 23.5 ?g/ml against 3D7, respectively. Its inhibition of the resistant strain (K1) was also much better compared to its inhibition of the sensitive strain (3D7), indicated that the leaves of E. variegata to be potential as antimalarial agents, but its lower potency compared to artemisinin and chloroquin.